Silver Against the Coronavirus Epidemic = Серебро против эпидемии коронавирусов - Zhukov Аnatoliy; Zukow, Walery (Journal of Education, Health and Sport, 2020)
All over the world, research is currently underway aimed at finding the means of treatment and prevention of Covid-19 coronavirus disease . In such a situation, any new or long-known idea may be valuable. The purpose of this article is to draw the attention of medical science to the use of drugs based on silver compounds. One of the authors of the article is not a doctor, but as an experienced chemist, he has been developing and privately using silver compounds for the treatment of close relatives and friends for many years. Based on the foregoing, we consider it possible to offer for research treatment with silver inhalation with or without additional exposure to ultrasound (sound) and / or electrophoresis. We will offer interested organizations the composition of an ionic silver solution, which allows varying concentrations over a wide range. Mentioned composition is characterized by low cost and high stability over time. Во всём мире сейчас интенсивно ведутся исследования, направленные на поиск средств лечения и профилактики заболевания коронавирусом Covid-19. В такой ситуации может оказаться ценной любая новая или давно известная идея. Целью данной статьи является привлечение внимания медицинской науки к использованию препаратов на основе соединений серебра. Один из авторов статьи не является медиком, но как опытный химик, много лет занимался разработкой и приватным применением серебряных составов для лечения близких родственников и друзей. Исходя из перечисленного, считаем возможным предложить для проведения исследований лечение ингаляцией серебра с дополнительным воздействием, или без него, ультразвука (звука) и/или электрофореза. Заинтересованным организациям предложим состав раствора ионного серебра, позволяющего варьировать концентрации в широких пределах. Упомянутый состав отличается низкой стоимостью и высокой стабильностью во времени. Key words: epidemic; pandemic; treatment of coronavirus complications; coronavirus SARS-CoV-2; Covid-19; silver compounds; inhalation; electrophoresis; ultrasound. Ключевые слова: эпидемия; пандемия; лечение осложнений коронавируса; coronavirus SARS-CoV-2; Covid-19; соединения серебра; ингаляция; электрофорез; ультразвук.